Oral magnesium reduces gastric mucosa susceptibility to injury in experimental diabetes mellitus. Issue 2 (June 2016) - Ige, A.O.; Adewoye, E.O.; Okwundu, N.C.; Alade, O.E.; Onuobia, P.C.
Abstract: This study investigated the effect of magnesium on the gastric defence mechanism in alloxan-diabetic male Wistar rats. Sixty rats were randomly divided into 2 groups, A (n = 40) and B (n = 20). Each group was subdivided into control, diabetic untreated (DU), diabetic magnesium (250 mg/kg) treated (DMg250) and diabetic insulin (3 IU/kg s.c) treated (DI). Diabetes was induced with alloxan (120 mg/kg) and both groups were treated for 14 days. By day 14, group A rats were sacrificed, the stomach excised and evaluated for histopathology, mucus content, parietal and mucus cell counts. Blood was withdrawn from the orbital sinus of group B rats for biochemical evaluation (blood glucose, superoxide dismutase (SOD), lipid peroxidation (LP) and nitric oxide (NO)) and later sacrificed for gastric SOD, LP and NO evaluation. Blood glucose level was reduced (p < 0.05) in all treatment groups compared to DU. Gastric SOD, parietal and mucus cell counts were increased (p < 0.05) in the DMg250 and DI compared to DU. Serum LP and NO were reduced while gastric LP was increased in the DMg250 compared to DU. Gastric NO and mucous content were significantly reduced (p < 0.05) in all diabetic groups compared to control. The gastric mucosa of the DU group had haemorrhage, inflammation and parasites embedded. The DMg250 and DI had normal submucus and muscle layers with reduced inflammation. Oral magnesium treatment in diabetes exerts hypoglycaemic effects, reduces serum nitric oxide and lipid peroxidation, increases gastric superoxide dismutase, mucous cell count and reduces the susceptibility of the gastric mucosa to ulceration.